Effects of hot water and calcium lactate treatments on fresh-cut quality of papaya - َAmin Mirshekari (University of Birjand, 2021)
Purpose: Papaya is one of the most common fruits which has been produced in southern part of Iran for fresh consumption. Demand for fresh-cut products has increased due to the changes in consumer attitudes. However, fresh-cut papaya is prone to softening during storage. This study carried out to determine effects of calcium lactate and hot water treatments (HWT) for maintaining fresh-cut papaya quality. Research method: After preparing fresh cut cubes of papayas, the pieces were dipped in calcium lactate (CaL) or combined with HWT. Physico-chemical parameters including calcium concentration (Ca), firmness and soluble solids concentration, catalase and peroxidaseactivities, pectin methyl esterase (PME) and polygalacturonase activities (PG),total phenolic content and radical scavenging activities, and microbial growth were measured during 9 days of storage at 5 ◦C. Findings: At the end of storage, CaL treatment combined with HWT increased calcium (Ca) concentration, catalase activity, total phenolic content and radical scavenging activities (DPPH) of papaya slices, but decreased peroxidase, PG and PME activities compared to the control. In addition, these treatments reduced microbial growth compared to the control. Limitations: No limitations were encountered. Originality/Value: Both HWT with CaL showed potential for increasing markeabitity on fresh cut papaya with their generally recognized as safe status for consumers.